Telepresence Enclosure - Paul Roquet (Media Theory)
Virtual reality proponents often promise the technology will allow a more fully embodied sense of presence at a distance, or what researchers have called ‘telepresence.’ Departing from telepresence’s original focus on providing access to dangerous environments, VR and robotics researchers in Japan now promote everyday service and factory work via telerobots as a solution to the country’s rapidly shrinking workforce. Telepresence becomes a way to access the physical labor of the elderly, persons with disabilities, and foreign workers, while at the same time keeping them fixed in place at home or behind closed borders. This essay theorizes the perceptual segregation imposed by these immersive labor platforms as a form of telepresence enclosure: the mediated privatization of presence itself. If VR continues on its current trajectory, the telepresence enclosure is poised to enable technologically advanced countries to extract the physical labor of marginalized populations at home and abroad, while at the same time ensuring these workers remain excluded from a more fully embodied social mobility.